2020
DOI: 10.3390/fluids5030155
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Convection in Metal Foams: A Survey and New CFD Results

Abstract: Metal foams are widely studied as possible tools for the enhancement of heat transfer from hot bodies. The basic idea is that a metal foam tends to significantly increase the heat exchange area between the hot solid body and the external cooling fluid. For this reason, this class of porous materials is considered as a good candidate for an alternative to finned surfaces, with different pros and cons. Among the pros, we mention the generally wider area of contact per unit volume between solid and fluid. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The pressure drop and the volumetric interphase heat Besides the mechanical properties, the investigation of the heat and mass transfer performances of a TPMS is also relevant. The numerical simulation of the heat and mass transfers for this type of engineered metal foam is reported in [46], where the analysis of the thermal entrance region in a gyroid TPMS based channel is carried out. The flow model employed for the local momentum balance equation is based on the Navier-Stokes equations while, for the local energy balance, it is based on a convection/conduction equation.…”
Section: Metal Foams As An Engineered Periodic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The pressure drop and the volumetric interphase heat Besides the mechanical properties, the investigation of the heat and mass transfer performances of a TPMS is also relevant. The numerical simulation of the heat and mass transfers for this type of engineered metal foam is reported in [46], where the analysis of the thermal entrance region in a gyroid TPMS based channel is carried out. The flow model employed for the local momentum balance equation is based on the Navier-Stokes equations while, for the local energy balance, it is based on a convection/conduction equation.…”
Section: Metal Foams As An Engineered Periodic Structurementioning
confidence: 99%
“…The first study on the slip condition in the Kelvin cells is reported Figure 6. Pressure drop, left hand side frame; and volumetric interphase heat transfer coefficient, (compared with the paper by [47]) right hand side frame; as functions of the inlet velocity [46].…”
Section: Metal Foams As An Engineered Periodic Structurementioning
confidence: 99%
“…In paper [114], the influence of the TPMS on heat transfer and water flow resistance in the structure of the sheet gyroid that was 2 × 2 × 10 (10 × 10 × 50 mm) was numerically investigated. StarCCM+ 2019.2 software and the volume-averaged model were adopted to solve the momentum and energy transfer.…”
Section: Heat Dissipation and Heat Sinkmentioning
confidence: 99%
“…Modeling and simulation have been used commonly for the study of cellular metals. These types of computational tools have generally been led toward the study of their mechanical [32] or physical properties [33], with few reports related to their use in their manufacturing. Most research are concentrated on closed-pore foams processing, on topics such as bubble decay analysis, bubble expansion, and foam solidification obtained with foaming agent [34][35][36].…”
Section: Introductionmentioning
confidence: 99%